Hysterical disorder of the person: history, clinic and psychotherapy peculiarities - Prostomolotov, Valerii (Psychiatry, Neurology and Medical Psychology, 2018)
The article describes hysteria, the oldest of all personality disorders that look different on different social floors. They are many of them among the lower strata of society. But they are also found among the middle class and even the elite. Outstanding hysterics can be found among historical figures, people’s idols, heroes, leaders: for example, Joan of Arc. The author considers hysterical personality disorder as a pathological development within the framework of a particular congenital constitution and introduces its specifications for the detection of obligate hysterical symptoms, including dissociative disorders. Methods of psychotherapy in the treatment of hysterical disorders fit into three areas: 1) the patient must understand what and why is happening to him; 2) he / she must learn to possess muscle and emotional-autonomic self-regulation; 3) he / she must learn to live, not to be treated, to realize hi / her potential of person and citizen.